Characterizing the Performance of Gas-Permeable Membranes as an Ammonia Recovery Strategy from Anaerobically Digested Dairy Manure - Melanie Fillingham; Andrew VanderZaag; Jessica Singh; Stephen Burtt; Anna Crolla; Chris Kinsley; J. Douglas MacDonald (Membranes, 2017)
Capturing ammonia from anaerobically digested manure could simultaneously decrease the adverse effects of ammonia inhibition on biogas production, reduce reactive nitrogen (N) loss to the environment, and produce mineral N fertilizer as a by-product. In this study, gas permeable membranes (GPM) were used to capture ammonia from dairy manure and digestate by the diffusion of gaseous ammonia across the membrane where ammonia is captured by diluted acid, forming an aqueous ammonium salt. A lab-scale prototype using tubular expanded polytetrafluoroethylene (ePTFE) GPM was used to (1) characterize the effect of total ammonium nitrogen (TAN) concentration, temperature, and pH on the ammonia capture rate using GPM, and (2) to evaluate the performance of a GPM system in conditions similar to a mesophilic anaerobic digester. The GPM captured ammonia at a rate between 2.2 to 6.3% of gaseous ammonia in the donor solution per day. Capture rate was faster in anaerobic digestate than raw manure. The ammonia capture rate could be predicted using non-linear regression based on the factors of total ammonium nitrogen concentration, temperature, and pH. This use of membranes shows promise in reducing the deleterious impacts of ammonia on both the efficiency of biogas production and the release of reactive N to the environment.